Activating the Role of Financial Management In Public and Private Hospitals in Irbid and Al- Mafraq Governorates in Jordan A Field Study - Smadi, Ziad; Al-Awawdeh, Waleed (The Arab Journal of Administration, 2018)
The study aimed to identify to which extent the hospitals is having specialized administrative units to the function of financial management, and to identify the existence of a formal job description for the post of financial management. It also aimed to identify the methods and tools adopted by the financial managers’ officer in performing their jobs, as well as to identify the goals and objectives adopted by the financial management units. The study sample consisted of all the (21) hospitals working in Irbid and Al- Mafraq governorates, the questionnaire were distributed equally to these hospitals, about (2) questionnaire for each hospital. They were distributed to managers of financial management or his deputy, or to the supervisors of Accounting or Auditing departments and if not found, it was distributed to general managers of these hospitals. The study result revealed that the existence of a specialized administrative unit function of financial management in most hospitals of study sample, usually these units were linked directly to the hospital administrative director, also most of workers working in the financial management units were a bachelor’s degree holder in accountancy , the study also revealed that the methods and tools of the financial managers rely on in his performance is by comparing his past performance with present performance. The study recommended a set of recommendations, the most important of these are the need to emphasize the existence of a specialized management function of financial management in all government and private hospitals, and the need to emphasize of linking the financial units with the senior management of these hospitals because of the great importance of financial management in hospital management and in the performance of its functions, and they must better activate the role of these financial units at these hospitals.